IDENTIFIKASI ANTIBODI SPESIFIK Toxoplasma gondii PADA WANITA DI KOMUNITAS PECINTA SUGAR GLIDER INDONESIA (KPSGI) KOTA MAKASSAR - Dzikra Arwie; Rahmat Aryandi (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
This research is motivated by quite a lot of public interest in maintaining pet animals such as sugar gliders but the negative effects of these animals can cause zoonotic diseases such as toxoplasmosis caused by the parasite Toxoplasma gondii. However, the presence of Toxoplasma gondii specific antibodies against sugar glider lovers is not known with certainty. This study aims to identify specific Toxoplasma gondii antibodies in women in the Makassar Sugar Glider Indonesia (KPSGI) Lovers community. The study was a laboratory observation with qualitative analysis techniques with the research subjects being women in the sugar glider (KPSGI) lover community in Makassar. Of the 10 samples taken by purposive sampling technique, 40% of female samples were obtained in the body with Toxoplasma gondii specific antibodies.